An updated review of Terminalia catappa - Anand, Arumugam Vijaya; Divya, Natarajan; Kotti, Pannerselvam Punniya (Pharmacognosy Reviews)
Terminalia catappa Linn. is known for its nutritional fruit and possesses medicinal benefits as well. This is a comprehensive review of the phytoconstituents and pharmacological benefits. T. catappa has been recognized for its medicinally essential phytoconstituents, such as phenol, flavonoid, and carotenoid. Numerous pharmacological investigations have confirmed this plant’s ability to exhibit antimicrobial, anti‑inflammatory, antidiabetic, antioxidant, hepatoprotective, and anticancer activities, all of which support its traditional uses.
Keywords: Anticancer; antidiabetic; antioxidant; hepatoprotective; Terminalia catappa